Active transitive impersonals in Slavic and beyond: a parallel corpus analysis = Aktivnye perechodnye bezličnye konstrukcii v slavjanskich i drugich jazykach : analiz parallelʹnogo korpusa - Schlund, Katrin (Russian linguistics, 2020)
Morphologically unmarked transitive (or accusative) impersonals, often also referred to as Adversity Impersonals or Elemental Constructions, have long been considered a primarily East Slavic phenomenon, with a somewhat marginal status in Polish. More recent research has claimed that these impersonal constructions also occur in other West Slavic languages and even in Slovenian. The present paper refines some of the previous assumptions about morphologically unmarked transitive impersonals in twelve Slavic and two non-Slavic languages by drawing on the results of a parallel corpus study. The analysis of empirical data suggests that it is necessary to identify the Štokavian dialectal continuum as a transitional area with a declining acceptability of morphologically unmarked transitive impersonals from the Northwest (Croatian) to the Southeast (Serbian). Moreover it will be shown that impersonals of this type are not an exclusively Slavic phenomenon
Online veröffentlicht: 30. März 2020
Gesehen am 15.10.2025